2022
DOI: 10.1002/ange.202116171
|View full text |Cite
|
Sign up to set email alerts
|

Dearomative Cyclopropanation of Naphthols via Cyclopropene Ring‐Opening

Abstract: The dearomatization of 2‐naphthols represents a simple method for the construction of complex 3D structures from simple planar starting materials. We describe a cyclopropanation of 2‐naphthols that proceeds via cyclopropene ring‐opening using rhodium and acid catalysis under mild conditions. The vinyl cyclopropane molecules were formed with high chemoselectivity and scalability, which could be further functionalized at different sites. Both computational and experimental evidence were used to elucidate the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…1a). 4 This exciting progress revealed that cyclopropenes are perhaps the most widely used building blocks in the creation of new cyclopropane-based molecular structures. Indeed, catalytic and direct functionalizations of cyclopropenes have provided numerous convergent and very flexible approaches for the preparation of a large variety of substituted alkyl-, alkynyl-, vinyl-, and arylcyclopropanes in good diastereo- and enantiomeric ratios.…”
Section: Introductionmentioning
confidence: 99%
“…1a). 4 This exciting progress revealed that cyclopropenes are perhaps the most widely used building blocks in the creation of new cyclopropane-based molecular structures. Indeed, catalytic and direct functionalizations of cyclopropenes have provided numerous convergent and very flexible approaches for the preparation of a large variety of substituted alkyl-, alkynyl-, vinyl-, and arylcyclopropanes in good diastereo- and enantiomeric ratios.…”
Section: Introductionmentioning
confidence: 99%